Temperature effect on expression of soluble Endoglucanase I from Fusarium oxysporum using E. coli Lemo21:DE3 - Noor Batcha, Ibrahim Ali; Raja Izzuddin, Raja Hawa Nurathirah; Ahmad, Abdul Aziz; Mohd Salleh, Hamzah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
Formation of inclusion bodies especially when expressing eukaryotic recombinant proteins in prokaryotic host such as E. coli is a challenge. Ability to express soluble proteins in E.coli will enable us to utilize all the benefits of E.coli as a host mainly the short doubling time. As few reports indicates that temperature influences the expression of recombinant proteins, this study aims to observe its effect on solubility of endoglucanase I. The optimum temperature for expressing endoglucanase I from Fusarium oxysporum using Lemo21:DE3 as a host is reported here.